Quality of Life in Long-Term, Disease-Free Survivors of Breast Cancer: a Follow-up Study - Peter Ganz (2002)
Background: Women with breast cancer are the largest group of female survivors of cancer. There is limited information about the long-term quality of life (QOL) in disease-free breast cancer survivors. Methods: Letters of invitation were mailed to 1336 breast cancer survivors who had participated in an earlier survey and now were between 5 and 10 years after their initial diagnosis. The 914 respondents interested in participating were then sent a survey booklet that assessed a broad range of QOL and survivorship concerns. All P values were two-sided. Results: A total of 817 women completed the follow-up survey (61% response rate), and the 763 disease-free survivors in that group, who had been diagnosed an average of 6.3 years earlier, are the focus of this article. Physical well-being and emotional well-being were excellent; the minimal changes between the baseline and follow-up assessments reflected expected age-related changes. Energy level and social functioning were unchanged. Hot flashes, night sweats, vaginal discharge, and breast sensitivity were less frequent. Symptoms of vaginal dryness and urinary incontinence were increased. Sexual activity with a partner declined statistically significantly between the two assessments (from 65% to 55%, P = .001). Survivors with no past systemic adjuvant therapy had a better QOL than those who had received systemic adjuvant therapy (chemotherapy, tamoxifen, or both together) (physical functioning, P = .003; physical role function, P = .02; bodily pain, P = .01; social functioning, P = .02; and general health, P = .03). In a multivariate analysis, past chemotherapy was a statistically significant predictor of a poorer current QOL (P = .003). Conclusions: Long-term, disease-free breast cancer survivors reported high levels of functioning and QOL many years after primary treatment. However, past systemic adjuvant treatment was associated with poorer functioning on several dimensions of QOL. This information may be useful to patients and physicians who are engaging in discussion of the risks and benefits of systemic adjuvant therapy.